FROM ACCOMMODATION TO REPRESSION: THE EVOLUTION OF POLITICAL ISLAM IN DEMOCRATIC INDONESIA DURING SBY AND JOKOWI PRESIDENCIES - Krismono, Krismono (Politea : Jurnal Politik Islam, 2024)
This study examines the evolution of political Islam in Indonesia during the presidencies of Susilo Bambang Yudhoyono (SBY) and Joko Widodo (Jokowi), focusing on the shift from accommodation to repression. During the SBY era (2004-2014), the government adopted an accommodative approach towards Islamic groups, engaging moderate organizations such as Nahdlatul Ulama and Muhammadiyah as strategic partners in maintaining social stability. However, conservative groups began to challenge the democratization agenda. In contrast, Jokowi's administration (2014-2024) has faced increasingly complex challenges due to the rise of Islamic populism and identity politics, as exemplified by Aksi Bela Islam (ABI) 212. In response, Jokowi implemented more assertive measures, such as banning the HTI and FPI, to safeguard national stability and prevent radicalization. This study employs a qualitative descriptive approach and a literature review to analyze the dynamics of political Islam's rise and transformation during these two periods. The findings reveal that SBY's accommodative policies created relative stability but compromised pluralism, while Jokowi's repressive approach exacerbated political polarization. The study concludes that the evolution of political Islam reflects a dynamic process in which the state must balance Islamic aspirations, democratic commitments, and the need for stability amidst the increasing challenges to pluralism. Understanding these shifts is essential for comprehending the complex relationship between Islam, democracy, and national stability in Indonesia